Let $a_1,\ldots,a_r\in R$ be elements of a commutative ring and let $x$ be a variable. We form the polynomial

$$\begin{array}{rcl}p(x)&:=&(x-a_1)\cdots (x-a_r)\\

&=&x^r+(-1)^1\Sigma_1x^{r-1}+(-1)^2\Sigma_2x^{r-2}+\ldots+(-1)^{r-1}\Sigma_{r-1}x+(-1)^{r}\Sigma_r

\end{array}$$

The coefficients $\Sigma_1,\ldots,\Sigma_r$ are called **elementary symmetric** functions $\Sigma_k:R^r\to R$, which are defined as sums

$$\begin{array}{rcl}

\Sigma_1(a_1,\ldots,a_r)&:=&\sum_{1\le k\le r}a_k\\

\Sigma_2(a_1,\ldots,a_r)&:=&\sum_{1\le k < l\le r}a_ka_l\\

\Sigma_3(a_1,\ldots,a_r)&:=&\sum_{1\le k < l < m\le r}a_ka_la_m\\

\vdots&&\\

\Sigma_r(a_1,\ldots,a_r)&:=&a_1\cdots a_r\\

\end{array}$$

| | | | | created: 2019-04-07 21:11:02 | modified: 2019-04-07 21:57:34 | by: *bookofproofs* | references: [6735]

(none)

[6735] **Lang, Serge**: “Algebra – Graduate Texts in Mathematics”, Springer, 2002, 3rd Edition

FeedsAcknowledgmentsTerms of UsePrivacy PolicyImprint

© 2018 Powered by BooOfProofs, All rights reserved.

© 2018 Powered by BooOfProofs, All rights reserved.